Novel deletions of 14q11.2 associated with developmental delay, cognitive impairment and similar minor anomalies in three children. Issue 9 (1st June 2007) - Zahir, Farah; Firth, Helen V; Baross, Agnes; Delaney, Allen D; Eydoux, Patrice; Gibson, William T; Langlois, Sylvie; Martin, Howard; Willatt, Lionel; Marra, Marco A; Friedman, Jan M
Abstract : Methods and results: We identified de novo submicroscopic chromosome 14q11.2 deletions in two children with idiopathic developmental delay and cognitive impairment. Vancouver patient 5566 has a ∼200 kb deletion and Vancouver patient 8326 has a ∼1.6 Mb deletion. The Database of Chromosomal Imbalance and Phenotype in Humans using Ensembl Resources (DECIPHER) revealed a third patient with idiopathic developmental delay and cognitive impairment, DECIPHER patient 126, who has a ∼1.1 Mb deletion of 14q11.2. The deletion of patient 5566 overlaps that of patient 126 and both of these deletions lie entirely within that of patient 8326. All three children have similar dysmorphic features, including widely-spaced eyes, short nose with flat nasal bridge, long philtrum, prominent Cupid's bow of the upper lip, full lower lip and similar auricular anomalies. Conclusion: The minimal common deletion region on chromosome 14q11.2 is only ∼35 kb (from 20.897 to 20.932, University of California at Santa Cruz (UCSC) Genome Browser; build hg18, March 2006) and includes only two genes, SUPT16H and CHD8, which are good candidate genes for the phenotypes. The non-recurrent breakpoints of these patients, the presence of normal copy number variants in the region and the local genomic structure support the notion that this region has reduced stability.